ROAD TRANSPORT INFORMATION SERVICES - RTIS - Kramarčík, Marek (Doprava a spoje, 2006)
In this paper I wanted to stress the development of navigation and communication technologies in RTIS. In near future especially car navigation systems will distinctly influence information services in road transport, today in unforeseeable extent.